Pengaruh Ketepatwaktuan dan Pengendalian Internal Terhadap Kebermanfaatan Informasi Akuntansi Akrual: Studi Empiris pada Satuan Kerja Perangkat Daerah Kota Padang - Thesha Grasiana Sihaloho; Fefri Indra Arza (Universitas Negeri Padang, 2024)
This purpose of this study was to the influence of timeliness and internal control on the usefulness of accrual accounting information. Respondents in this research were Heads of Departments, Head of Finance Subdivision and treasurers at SKPD Padang City. The sample determination method uses purposive sampling. The sample in this study was obtained by distributing a total of 96 questionnaires and 88 questionnaires that could be processed. The data analysis method used is multiple linear regression analysis with the help of IBM SPSS 25 software. The results of this research show that timeliness and internal control have an influence on the usefulness of accrual accounting information.